2014
DOI: 10.1111/gcb.12432
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency fire alters C : N : P stoichiometry in forest litter

Abstract: Fire is a major driver of ecosystem change and can disproportionately affect the cycling of different nutrients. Thus, a stoichiometric approach to investigate the relationships between nutrient availability and microbial resource use during decomposition is likely to provide insight into the effects of fire on ecosystem functioning. We conducted a field litter bag experiment to investigate the long-term impact of repeated fire on the stoichiometry of leaf litter C, N and P pools, and nutrient-acquiring enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 64 publications
(88 reference statements)
10
54
0
Order By: Relevance
“…With these values at the beginning and at the end of the decomposition process, the slope is found as β = −0.04. This trend implies an increasing microbial biomass N:C as decomposition progresses and litter N:C ratio increases, as suggested by data (Wagener and Schimel, 1998; van Meeteren et al, 2008; Brandstäetter et al, 2013; Toberman et al, 2014). Moreover, with this parameterization of model III, the value of r B at x = 0.5 is consistent with the long-term average r B = 0.1 assumed for models I and II.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…With these values at the beginning and at the end of the decomposition process, the slope is found as β = −0.04. This trend implies an increasing microbial biomass N:C as decomposition progresses and litter N:C ratio increases, as suggested by data (Wagener and Schimel, 1998; van Meeteren et al, 2008; Brandstäetter et al, 2013; Toberman et al, 2014). Moreover, with this parameterization of model III, the value of r B at x = 0.5 is consistent with the long-term average r B = 0.1 assumed for models I and II.…”
Section: Methodssupporting
confidence: 57%
“…However, in decomposing litter undergoing strong nutrient enrichment, some trends in microbial biomass N:C have been found. In some studies, microbial N:C increases with increasing litter N:C as decomposition progresses (Wagener and Schimel, 1998; van Meeteren et al, 2008; Brandstäetter et al, 2013; Toberman et al, 2014), but in others no trends are apparent (Mooshammer et al, 2014a). Along the extreme stoichiometric gradient between a decaying log and the nearby soil (assuming that the latter is representative of the final phases of wood decomposition), only small differences in microbial biomass elemental composition were found, despite the four-fold increase in N:C ratio (Hart, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly in forest ecosystems, fires tend to reduce soil organic matter and nutrient availability in the short term, although the addition of burnt plant material can increase these parameters in the long-term (PrietoFernández et al, 2004;Certini, 2005). Williams et al (2011) andToberman et al (2014) observed that a greater frequency in prescribed fires lead to greater loss in available soil nutrients in the long-term. We observed no, or only minimal, differences in the soil parameters (pH, total N, and total C) across the different burn treatments, even though our experimental manipulations have been in place for two decades.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment consisted of 4 randomized burning plots (as described by Toberman et al. ), with 12 burning plots in total. Each of these burning plots was ca.…”
Section: Methodsmentioning
confidence: 99%
“…Recent or repeated fire events are often associated with N‐depleted and P‐enriched stoichiometry (i.e., lower N : P and C : P) in soil and plant material (Toberman et al. , Muqaddas et al. , Butler et al.…”
Section: Introductionmentioning
confidence: 99%